ANALISIS KARAKTER SISWA DAN KEMAMPUAN GURU MENGAITKAN SAINS DENGAN AL-QUR’AN DALAM PEMBELAJARAN IPA - Wawan Prasetyo Heryanto (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2019)
An application of students’ character education in a learning process is a must for teachers. It aims to build good values especiallyreligious, nationalist, mutual cooperation, integrity, and independence.This research was conducted to determine the students’ character in Muhammadiah 1 Junior High School and the teachers’ ability to associate science with Al-Qur’an. The method used was descriptive qualitative method using observation instruments, interviews, and student character questionnaires.Based on the results obtained, the research showed that the teachers had carried out the learning process well and beginning with the preparation of learning devices.The teachers had time management in applying the Qur'anic science approach.The highest average students character scorewas 78 for religious valuesin the ninth grade, and the lowest score was 52 for independence value in the seventh grade.